Non-scale-invariant inverse curvature flows in hyperbolic space - Scheuer, Julian (Calculus of variations and partial differential equations, 2015)
We consider inverse curvature flows in hyperbolic space $$\mathbb {H}^{n+1}$$Hn+1with starshaped initial hypersurface, driven by positive powers of a homogeneous curvature function. The solutions exist for all time and, after rescaling, converge to a geodesic sphere.